Effect of AI-based pre-hospital health education via QR code on APAIS scores in patients with breast nodules: A retrospective study - Guozhen Ma; Chuyuan Miao; Pengjun Jiang; Guiqing He; Huiping Li; Yanhui Huang; Huiwen Yu; Tianwen Chen (Breast)
Purpose: To explore the effect of AI-based pre-hospital health education via QR code on preoperative anxiety and information needs in patients with breast nodules and provide a decision-making reference for ongoing optimizing clinical workflows. Methods: This retrospective study analyzed the clinical data of 718 breast nodule patients from January to December 2024. Patients were sequentially divided into a non-viewed group (receiving routine health education) and a viewed group (receiving AI-based pre-hospital health education) to compare Amsterdam Preoperative Anxiety and Information Scale (APAIS) scores between the two groups. Univariate analysis and multivariate regression were used to examine factors influencing preoperative anxiety and information needs in patients with breast nodules. Results: 718 patients were included, with 367 in the non-viewed group and 351 in the viewed group. Patients in the viewed group reported higher satisfaction scores and had shorter hospital stay compared to those in the non-viewed group. The multiple linear regression analysis revealed a significant negative correlation between the viewed group and preoperative anxiety (β = −5.31, 95 % CI: −6.03, −4.59; P = 0.001) and information needs (β = −1.40, 95 % CI: −1.63, −1.18; P = 0.001). Additionally, patient satisfaction also influences their preoperative anxiety and information needs (P < 0.001). Conclusion: AI-based pre-hospital health education can help reduce patients with breast nodules' preoperative anxiety and information needs, as well as increase their satisfaction and shorten hospital stay. AI-based pre-hospital health education via QR code can be applied in clinical practice.